A Study of Human Resource Capability for Enhancing Local Food-Processing Entrepreneur’s Performance among Community-Based Enterprises - Kruasom , Taisith; Khumhome, Bussakorn (Journal of Ecohumanism, 2025)
This research explores the human resource (HR) capabilities that reinforce performance and resilience in community-based enterprises (CBEs). Locally, the food-processing sector, specifically focusing on the provinces of Ubon Ratchathani, Yasothon, Amnat Charoen, and Si Sa Ket, serves as the focus of this study. Adopting a qualitative research methodology based on acceptable criteria, the researchers conducted three rounds of purposive sample selection. Ultimately, 16 CBEs comprising 43 key informants were included in the study. Categorical data were gathered through diverse methods to ensure data saturation and mitigate bias. The approaches of focus groups, observations, face-to-face interviews, and analysis of relevant documentation were ethically employed. Thematic and content analyses were used to examine the data within the framework of HR capability and operational performance among CBE members. The findings derived from HR capability and their contributions to firm performance rely on several critical aspects, such as the importance of employee training and development, leadership effectiveness, strategies for motivation and retention, fostering a supportive organizational culture, implementing strategic HR practices, adapting to new technologies, leveraging external HR services, adhering to regulatory standards, promoting gender equality and inclusivity, and understanding economic influences. This study contributes to the theoretical understanding of strategic HR management by contextualizing these internal (HR) and external (economy) practices within CBEs. Additionally, it offers an essential agenda for practical recommendations to HR professionals and policymakers with a shared goal of advancing local and national growth and development. Importantly, it emphasizes achieving sustainable growth for CBEs and enhancing resilience in the food-processing sector